Experimental Study on Bending Stress of Spur Gear with Tooth Profile Modification and Finite Element Verification - Chen Xueshi; Tang Jinyuan; Chen Siyu; Fu Zhihong (Jixie chuandong)
The study of static and dynamic meshing characteristics of gears has high theoretical value for improving gear carrying capacity and dynamics performance. The influence of tooth profile modification on bending stress is studied by experiment and finite element. The standard FZG gear drive test rig is used to measure the bending stress of the tooth root,and carbon slip rings is used to measure the bending stress of the tooth root dynamically. The main conclusions from the test and finite element analysis are as follow: the tooth profile modification can obviously reduce the tooth bending stress of the gear pair during the gear transmission,the higher the rotational speed of the gear pair,the more obvious the improvement of the bending stress of the tooth profile modification.